Prevention of Women Harassment and Fight For Human Rights-A Study on Me Too Movement by the Views of Media - CHAKRABORTY, NANDINI; BASU, PROF. DR. TAPATI (The journal of contemporary issues in business and government, 2021)
The Me Too movement focuses on the experiences of sexual violence survivors. Me Too movement works on empowerment through empathy by showing the planet just how common harassment is and by telling survivors that they aren’t alone — and are supported. Various researches show, how media support uplifted a group movement into a social movement. The movement has provided a source of solidarity for ladies from all backgrounds who have experienced harassment.